On One Method for the Introduction of Local Coordinates in a Neighborhood of an Invariant Toroidal Set - Davydenko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We consider one method for the introduction of local coordinates in a neighborhood of an m-dimensional invariant torus of a dynamical system of differential equations in the Euclidean space R n in dimensions satisfying the inequalities m + 1 < n ≤ 2m.